Evidence of low‐temperature phase transition in BaTiO3‐modified NaNbO3: Raman spectroscopy study. (4th September 2019) - Jauhari, Mrinal; Mishra, Sanjay Kumar; Poswal, Himanashu Kumar; Mittal, Ranjan; Chaplot, Samrath Lal
Abstract: The solid solution of NaNbO3 modified by 5% BaTiO3 (NNBT05) is investigated by Raman spectroscopic technique as a function of temperature from 83 to 298 K. Detailed mode analysis revealed that the Raman bands at 112.8 and 277.1 cm −1 (at 298 K) disappear due to change in the symmetry of the structure at low temperature of 83 K. Further, rapid changes in the position of the Raman bands at 58.7 and 606.4 cm −1 (at 298 K) as a function of temperature provide evidence for the structural phase transition. These changes in the Raman spectra occur at different temperatures in the cooling and heating cycles as in a hysteresis loop, which provide evidence of the first‐order nature of the phase transition at low temperature. Abstract : The variation in the peak positions of the main translational and stretching band at 58.7 and 606.4 cm −1 respectively as a function of temperature showed hysteresis behaviour. This hysteresis behaviour provides direct evidence of the first‐order phase transition at low temperature for the modified sodium niobate NNBT05.